ChemInform Abstract: Extending the Substrate Scope for the Asymmetric Iridium‐Catalyzed Hydrogenation of Minimally Functionalized Olefins by Using Biaryl Phosphite‐Based Modular Ligand Libraries. Issue 33 (27th July 2016) - Pamies, Oscar; Magre, Marc; Dieguez, Montserrat
Abstract: Review: [32 refs.